Annual analysis of the performance of a PV module with a cooling system - Janowicz, Weronika; Pomorski, Michał (Instal, 2023)
This paper presents an analysis of the influence of weather conditions on the temperature of PV cells and the impact of that change of temperature on energy conversion’s efficiency and electrical energy generation. This paper also shows an analysis of performance of PV modules with a cooling system and the energetical benefits of usage of such systems. The analysis of cooling PV modules by extended finned heat exchange surface on the module’s back side and air-flow based cooling system is presented. The analyzed modules’ parameters are as follows: power of 410 W, efficiency in Standard Test Conditionsof 21.5%, temperature coefficient of power of – 0.34%/oC for one module and – 0.5%/oC for second analyzed module. The weather conditions are based on data provided by a meteorological station in Wroclaw. It was established that the maximum temperature of PV cell without cooling equaled 57oC, maximum efficiency equaled 24.4% and minimum efficiency 19.2% for module with temperature coefficient of – 0.34%/oC, however for the module with temperature coefficient of – 0.5%/oC those efficiencies vary from 25.8% to 18.1%. Extended heat exchange surface as a cooling system on the back side of the module decreases the maximum cell temperature to 35.2oC (at a ribbing degree of 10). Relative increase of generated electricity was calculated as 3.1% for module with temperature coefficient of – 0.34%/oC and 4.6% for module with temperature coefficient of – 0.5%/oC. Air-flow based cooling system of the back side of a module decreases the maximum cell temperature to 41.2oC (at a heat transfer coefficient of 50 W/m2K). Relative increase of generated was calculated as 2.1% for module with temperature coefficient of – 0.34%/oC and 3.1% for module with temperature coefficient of – 0.5%/oC. Calculated relative increase of generated energy applies to only one year of module’s functioning. It is significant that cooling PV modules has an impact on decreasing the amplitude of change of PV cell temperature which causes a decrease in thermal loads. It results in prolonged life span of such module, what suggests that generated power of a cooled module in its whole life could be significantly larger.
Keywords: photovoltaic module; cooling systems for PV modules; finned surface; air-flow based cooling system